Modeling of organic thin film field-effect transistors based on pentacene in saturation regime: Effect of light illumination - Mansouri, S.; Bourguiga, R.; Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2012)
Thin film transistor based on pentacene was fabricated on a SiO2/Si substrate by thermal evaporation method at room temperature. Electrical characteristics of the pentacene transistor subjected to a UV light excitation at a wavelength of 365 nm were analyzed. Using the variable range hopping model transport (VRH) we have reproduced the mobility of charge carriers under dark and under light illumination in saturation regime. We have presented a method (differential method) that we can extract electrical parameters of this transistor based on pentacene under dark and under light illumination from the first and the second numerical derivative of electrical measurement I-D(V-G). Finally, we have extracted the electrical parameters, conductance g(ch) and the total resistance R-T, of organic TFTs from output characteristics I-D(V-D) using numerical fit under dark. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Dependent Mobility; Emitting-Diodes; Temperature; Circuits; Octithiophene; Electrodes; Insulator; Display; Driven